Impact of lipoprotein(a) levels and apolipoprotein(a) isoform size on risk of coronary heart disease. (5th February 2014) - Hopewell, J. C.; Seedorf, U.; Farrall, M.; Parish, S.; Kyriakou, T.; Goel, A.; Hamsten, A.; Collins, R.; Watkins, H.; Clarke, R.; the PROCARDIS Consortium
Abstract Objectives Observational and genetic studies have shown that lipoprotein(a) [Lp(a)] levels and apolipoprotein(a) [apo(a)] isoform size are both associated with coronary heart disease (CHD) risk, but the relative independence of these risk factors remains unclear. Clarification of this uncertainty is relevant to the potential of future Lp(a)‐lowering therapies for the prevention of CHD. Methods Plasma Lp(a) levels and apo(a) isoform size, estimated by the number of kringle IV (KIV) repeats, were measured in 995 patients with CHD and 998 control subjects. The associations between CHD risk and fifths of Lp(a) levels were assessed before and after adjustment for KIV repeats and, conversely, the associations between CHD risk and fifths of KIV repeats were assessed before and after adjustment for Lp(a) levels. Results Individuals in the top fifth of Lp(a) levels had more than a twofold higher risk of CHD compared with those in the bottom fifth, and this association was materially unaltered after adjustment for KIV repeats [odds ratio (OR) 2.05, 95% confidence interval (CI) 1.38–3.04, P < 0.001]. Furthermore, almost all of the excess risk was restricted to the two‐fifths of the population with the highest Lp(a) levels. Individuals in the bottom fifth of KIV repeats had about a twofold higher risk of CHD compared with those in the top fifth, but this association was no longer significant after adjustment for Lp(a) levels (OR 1.13, 95% CI 0.77–1.66, P = 0.94). Conclusions The effect of KIV repeats on CHD risk is mediated through their impact on Lp(a) levels, suggesting that absolute levels of Lp(a), rather than apo(a) isoform size, are the main determinant of CHD risk.